Strain-induced exciton redistribution among quantum emitters in two-dimensional materials - Giuseppe Ronco; Abel Martínez-Suárez; Davide Tedeschi; Matteo Savaresi; Aurelio Hierro-Rodríguez; Stephen McVitie; Sandra Stroj; Johannes Aberl; Moritz Brehm; Victor M. García-Suárez; Michele B. Rota; Pablo Alonso-González; et al. (npj 2D Materials and Applications)
Abstract The discovery of quantum emitters (QEs) in two-dimensional (2D) materials has triggered a surge of research to assess their suitability for quantum photonics. Although position-controlled QEs are routinely fabricated using static strain gradients, the use of dynamic strain fields to control the brightness of QEs has not been explored yet. Here, we address this challenge by introducing a novel device in which WSe2 monolayers are integrated onto piezoelectric pillars that provide both static and dynamic strains. The static strains are first used to induce the formation of QEs, while their energy and brightness are then controlled via voltages on piezoelectric pillars. Numerical simulations show that these effects are due to a strain-induced modification of the confining-potential landscape, which leads to a net redistribution of excitons among the different QEs. Our work provides a method to dynamically control the energy and brightness of QEs in 2D materials.